The influence of central corneal thickness and age on intraocular pressure measured by pneumotonometry, non-contact tonometry, the Tono-Pen XL, and Goldmann applanation tonometry. Issue 7 (17th June 2005) - Tonnu, P-A; Ho, T; Newson, T; El Sheikh, A; Sharma, K; White, E; Bunce, C; Garway-Heath, D
Abstract : Aims: To evaluate the influence of central corneal thickness (CCT) on intraocular pressure (IOP) measurements made with the Goldmann applanation tonometer (GAT), Tono-Pen XL, ocular blood flow tonograph (OBF), and Canon TX-10 non-contact tonometer (NCT). Methods: CCT was recorded for either eye (randomly selected) of each of 105 untreated patients with ocular hypertension and glaucoma attending the glaucoma research unit at Moorfields Eye Hospital. For each of the selected eyes, IOP was measured with the GAT (two observers), Tono-Pen, OBF, and NCT in a randomised order. The relation of measured IOP and of inter-tonometer differences with CCT and subject age was explored by linear regression analysis. Results: A significant association between measured IOP and CCT was found with each instrument. The change in measured IOP for a 10 μm increase in CCT was 0.28, 0.31, 0.38, and 0.46 for the GAT, Tono-Pen, OBF, and NCT, respectively (all p⩽0.05). There was a significant association between the NCT/GAT differences and CCT, with a tendency of NCT to overestimate GAT in eyes with thicker corneas. There was a significant association between GAT/Tono-Pen and OBF/Tono-Pen differences and age, with a tendency of GAT and OBF to overestimate the Tono-Pen in eyes of older subjects. Conclusion: IOP measurement by all four methods is affected by CCT. The NCT is affected by CCT significantly more than the GAT. Subject age has a differential effect on the IOP measurements made by the GAT and OBF compared to the Tono-Pen.